Epidemiology of cervical-root caries on teeth: High prevalence in the coca leaf chewing in the Andean people. - Etty Indriati Etty Indriati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2004)
Background: Cervical-root caries on teeth often called rampant caries or circular caries often suffered by children who consumed bottled sweet milk. In adult, cervical-root caries occurs in unique cases such as cancer patients who undertake chemotherapy, and narcotic addicts.Objective: The research was aimed to study the dental and oral health of Andean people who have traditionally been chewing coca-leaves as a part of their cultural and integral lives.Materials and Method: The subject of study was 210 Aymara people from highland Chile and Bolivia, Andes. They were given questionnaire whether they chew coca leaves or not. Without knowing whether one chewed coca leaves or not, each individual was examined for: the carious teeth, the caries location, the periodontal stage, the oral pH, the molar radices, the molar loss, and the total number of teeth preserved.Result: The result showed that people who chewed coca-leaves every day suffered cervical-root caries on their molar teeth, only radices of molars preserved, or even lost their molar teeth. They also suffered tongue desquamation and periodontal damage at the buccal area of molar teeth. In contrast, those who did not chew coca-leaves were relatively free from these dental disadvantages. Statistical analysis showed significantly high correlation between duration and intensity of chewing coca leaves with dental disadvantages (R=0,62 for molar loss; R=0,63 for bad periodontal status; and R =0,54 for cervical-root caries).Conclusion: It is concluded that habitual chewing of coca leaves damaged the periodontal region of the molar area, caused the root of the molar teeth to expose and led to cervical-root caries, then, only roots of molar preserved, and last, the lost of molar teeth. The high prevalence of cervical-root caries in coca-leaves chewers is in accord with other conditions such as cancer patients who undertake chemotherapy, and narcotic addicts. The alkaloid in the coca leaves are associated with the drying out the mouth leading to less self-cleansing and damaging the cervical-root area. Understanding the cultural tradition in a society is important if we were to understand the disease processes.Key words: coca leaves - Andes - epidemiology - cervical-root caries - molar